Rhetoric of Trauma and Recovery: Analyzing Sylvia Plath's Ariel - Dhungel, Mimamsha; Paudel, Sushil (Janabhawana Research Journal, 2025)
This study closely examines Sylvia Plath’s Ariel using trauma theory. It aims to understand how Ariel deals with psychological pain and the possibility of recovery. The study draws on the ideas of Cathy Caruth, Dominick LaCapra, and Judith Herman to explore the rhetorical and poetic techniques Plath uses to articulate trauma. The research focuses on selected poems: “The Applicant”, “Lady Lazarus”, “Tulips”, “Ariel”, “The Moon and the Yew Tree”, “The Arrival of the Bee Box”, “Poppies in July”, “Daddy” and “Edge.” It assesses how Plath’s poetic expressions are shaped by her personal experiences, examines the structural and thematic manifestations of trauma, and determines whether Ariel hints towards a narrative of healing or reinforces the inescapability of trauma and psychological suffering. The findings suggest that while there are strong indications of resilience and self-reclamation in Ariel, it mostly reflects both the fragmentation and repetition characteristic of trauma. The study highlights how memory, pain, and creativity intersect in Plath’s work by integrating trauma theory. Ultimately, the study situates Ariel not just as a work reflecting psychological suffering but also as a powerful testament to how poetry can be used as a cathartic medium.